A case of retroperitoneal schwannoma - Parikh, Jayesh V.; Dalal, Parth R.; Desai, Imran D.; Patel, Aquibjaved M. (International Surgery Journal, 2020)
Schwannoma are benign tumours of nerve sheath. They are also called as neurilemmoma. They are rare tumours arising from peripheral nerves, though they can occur anywhere on the body. Schwannoma can arise from any peripheral nerves or spinal nerves. Since they arise from nerve sheath forming schwannoma cells, they are never seen in brain or spinal cord. Schwannoma are often associated with neurofibromatosis-2, schwannomatosis and Carney complex where it is inherited in an autosomal dominant manner. They care often asymptomatic and diagnosed incidentally. Symptoms of schwannoma are related to pressure effects over the surrounding structures, such as limb pain, tingling and numbness, deafness and facial weakness as in vestibular schwannoma. However, most schwannoma are detected incidentally as in the case reported below. A 48 years female was diagnosed with an asymptomatic left para renal lump, which was later confirmed to be a retroperitoneal schwannoma. The patient had no complaints with respect to the lump. The patient underwent a successful surgical excision and had an uneventful recovery.